Emergency Contraception and Fertility awareness among University Students in Kampala, Uganda - Byamugisha, Josaphat K.; Mirembe, Florence M.; Faxelid, Elisabeth; Gemzell-Danielsson, Kristina (African health sciences, 2006)
Uganda has a high maternal mortality ratio with unsafe abortions being one of the major causes. Young people are particularly vulnerable to unsafe induced abortion with its sequelae. Emergency contraception (EC) may reduce unsafe abortions if easily accessible and acceptable. To determine knowledge about, ever use and attitudes towards EC among resident and non-resident female first year university students in Kampala. This Cross sectional study was carried out at Makerere University from January to March 2005.Out of 5971 females admitted in the academic year 2004/2005,379 answered a self administered questionnaire. The students were approached individually and given the questionnaire if they consented. Results: The mean age of the participants was 21 years. Less than half (45.1%) had ever heard about emergency contraceptive pills (ECPs).The most common sources of information about EC were friends (34%),media (24.8%) and schools (19.4%) .The ever pregnancy rate was 3.4 percent and 42 percent were in a steady relationship of three or more months. The contraceptive ever-use rate was 14.5 percent. Among the users the most common methods were condoms (48.9%) and withdrawal (23.4%). Emergency contraceptive pills had been used by seven students. Forty two percent did not know the time interval within which ECPs can work and one third thought it would interrupt an ongoing pregnancy. Thirty five percent did not know when in the menstrual cycle they were likely to conceive. The majority of the students were against over the counter (OTC) availability of EC because of fear of misuse. Knowledge about Emergency contraception and fertility awareness is low among the female first year university students. Friends and the media are an important source of EC information. Awareness and knowledge of EC should be increased.
Keywords: Emergency contraception; University students; Kampala